A comparative study of intravenous versus perineural administration of dexmedetomidine in supraclavicular brachial plexus block using 0.75% ropivacaine by ultrasound guided technique in upper limb surgeries - Khan, Fahad; Singh, V. P. (International Journal of Research in Medical Sciences, 2018)
Background: Comparative study of intravenous versus perineural administration of dexmedetomidine in supraclavicular brachial plexus block using 0.75% ropivacaine by ultrasound guided technique in upper limb surgeries. Methods: Patients in the age group 18-58 years both male and female, having ASA 1 and ASA 2, scheduled for elective surgery of unilateral upper limb surgeries were included and randomly divided into three groups’ i.e. group RD, group RDI and group R and patients with chronic pain or taking any analgesics, ASA grade III and IV, bleeding disorders, history of brachial plexus injury, known allergy to the study drug, previous shoulder surgery, any psychiatric disorders, peripheral neuropathy, failed block, significant respiratory disease, hearing impairment, pregnant women, study were excluded. Results: Time to sensory onset in group RD was as compared to group RDI and group R was found statistically significant (p<0.001). Duration of sensory block (analgesia) in group RD, group RDI and Group R was also statistically significant (p<0.001). The level of sedation of Group RDI and Group RD had highly significant value till 30 mins (p<0.001). Conclusions: The central effects of dexmedetomidine also play some role in prolongation of sensory and motor block duration, as explained previously.